2021
DOI: 10.1007/s13300-021-01114-x
|View full text |Cite
|
Sign up to set email alerts
|

Telemonitoring, Telemedicine and Time in Range During the Pandemic: Paradigm Change for Diabetes Risk Management in the Post-COVID Future

Abstract: People with diabetes are at greater risk for negative outcomes from COVID-19. Though this risk is multifactorial, poor glycaemic control before and during admission to hospital for COVID-19 is likely to contribute to the increased risk. The COVID-19 pandemic and restrictions on mobility and interaction can also be expected to impact on daily glucose management of people with diabetes. Telemonitoring of glucose metrics has been widely used during the pandemic in people with diabetes, including adults and childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 93 publications
1
34
0
Order By: Relevance
“…In the pediatric age, glucose metrics during lockdown were stable as compared to the pre-lockdown period in some studies [20,36,37] and significantly improved in others [20,38]. These results also sustain the role of technology for management of diabetes that may provide even greater aid during challenging condition as it has been recently reviewed [39]. This is further supported by the results of Longo et al [13] showing that subjects with type 1 diabetes on hybrid closed loop systems with telemedicine support had a significant improvement of metrics of glucose control during the pandemic lockdown.…”
Section: Discussionsupporting
confidence: 53%
“…In the pediatric age, glucose metrics during lockdown were stable as compared to the pre-lockdown period in some studies [20,36,37] and significantly improved in others [20,38]. These results also sustain the role of technology for management of diabetes that may provide even greater aid during challenging condition as it has been recently reviewed [39]. This is further supported by the results of Longo et al [13] showing that subjects with type 1 diabetes on hybrid closed loop systems with telemedicine support had a significant improvement of metrics of glucose control during the pandemic lockdown.…”
Section: Discussionsupporting
confidence: 53%
“… 67 As noted above in the patient and HCP surveys, the pandemic has driven a switch to remote monitoring and virtual consultation, both of which can be facilitated by the FreeStyle Libre system. Numerous published studies have demonstrated that glucose control did not deteriorate while access to regular diabetes clinical services was interrupted; and, in many cases, improved across selected metrics 68 including time in range, time above range, average glucose, and GMI.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies indicated that flash glucose monitoring was associated with successful diabetes management during enforced social distancing. 68 These include large studies in Scotland 69 and Spain 70 demonstrating that % time in range (%TIR) 3.9–10 mmol/L (70–180 mg/dL) over this period increased, with associated improvements in glycemic variability. Smaller studies across Europe involving groups of people with T1DM using the FreeStyle Libre system have typically shown improvements in %TIR and average glucose during enforced social distancing, 71–73 including for children and adolescents; 74 , 75 and, either improvement or no change in % time in hypoglycemia over the same period, including for groups at higher risk of hypoglycaemia.…”
Section: Resultsmentioning
confidence: 99%
“…A recent review of type 1 DM using telemonitoring and telemedicine during COVID-19 pandemic found that the majority of studies reported a significant improvement of time in range (TiR). 8 However, the review included both children and adults, as well as insulin pump patients and patients using multiple daily injections. 8 Moreover, the impact of ‘lock down’ might have affected the results.…”
Section: Introductionmentioning
confidence: 99%
“… 8 However, the review included both children and adults, as well as insulin pump patients and patients using multiple daily injections. 8 Moreover, the impact of ‘lock down’ might have affected the results. Only few studies have evaluated telemedicine for use in DM patients with an insulin pump.…”
Section: Introductionmentioning
confidence: 99%